Relaxation Modeling of PEO-b-PCL and its Component Polymers with PVPh at the Air/Water Interface - Pan, Hui-Ting; Hsu, Wen-Ping (Journal of Composites and Biodegradable Polymers, 2020)
The objective of this research was to find out the effects of structure of polyethylene oxide-block-polycaprolactone (PEO-b-PCL) and its component polymers and temperature on the iso-baric relaxation behaviors of mixed monolayers with poly(vinyl phenol). Iso-baric relaxation experiments of mixed monolayers at the air/water interface were investigated at different temperatures (10˚C, 25˚C and 40˚C). It was shown that most of the area relaxation process of mixed monolayers could be well represented by a model considering the nucleation and growth mechanisms. The characteristic exponent x values were found to be slightly temperature dependent. The kx values were detected to decrease with increasing temperature. When PVPh was added into the most unstable PEO, the mixed monolayer films exhibited a remarkably improved stable relaxation behavior than PCL( or PEO-b-PCL ). The stabilization behavior was likely caused by the PVPh-H2O-PEO interaction. There were likely less PVPh-H2O-PCL interaction since PCL interacted with PVPh favorably.